Kurt Schwitters : 12 Collagen + A. Jawlensky : Meditationen + Künstler der Galerie : Attersee - G. Brus - H. Nitsch - A. Rainer - D. Rot - G. Rühm - Editionen - Rühm, Gerhard (Wien : Galerie Klewan, 1976)
Jawlensky, Alexej V. ; Attersee ; Brus, Günter ; Nitsch, Hermann ; Rainer, Arnulf ; Rot, Dieter ; Rühm, Gerhard
boek
Keywords: Schwitters, Kurt